Familias monoparentais e vulnerabilidades: uma abordagem a partir dos Centros Municipais de Educação Infantil de Ponta Grossa - PR - 2007/2008 - Souza, Virginia de (2008)
This essay has as objective the study of the daily life of singled-parented families in social vulnerable situation addressed in the Municipal Center for Children Education. The families researched, besides being alone in their homes, have what literature points as social vulnerability. Along the essay the events which make families vulnerable have been discussed, analyzing the factors such as the weakening of relational-affective links, discrimination by gender, by territory and by disability. It has been evidenced which determinants hinder or facilitate the daily lives of these families with respect to education, maintenance and protection of children. Taking into account the CMEI’s researched in Ponta Grossa city – PR, it has been evidenced the existence of a relevant number of families which arrangements are singled-parented. Even with the prevalence of the nuclear and extended parenting arrangements, the single-parenting has become relevant as a social phenomenon. It is concluded that for the territory of Ponta Grossa – PR, the singled-parented arrangements conducted by the mother are predominant. The male income exceeds the female ones, however the women present a higher level of education compared to the researched men. The research pointed the existence of a primary net of solidarity which helps the families in many daily situations. Both the male and female parents use this support net, being the men the ones who use it for the care of the children and the women, the ones who use it for the cares and home financial support.